Investigation of the possible association of LRP5 gene polymorphisms with osteoporosis in an Indian subpopulation of Malda, West Bengal: a case-control study - Sengupta, Mrinmoyee; Ghosh, Bappaditya; Das, Mitali (International Journal of Research in Medical Sciences, 2025)
Background: The involvement of low-density lipoprotein receptor-related protein 5 (LRP5) in bone-related diseases with low bone mineral density like osteoporosis is scientifically well established. This study aims to explore the relationship between two LRP5 gene polymorphisms viz. rs3736228 (A1330V) and rs41494349 (Q89R) and the risk of osteoporosis in an Indian subpopulation. Methods: This case-control study included 61 patients with osteoporosis, and 30 healthy controls from Malda Medical College and Hospital. The SNP analysis was performed by PCR-RFLP method with DraIII and AvaII enzymes for rs3736228 (A1330V) and rs41494349 (Q89R) respectively. The data is validated with DNA sequencing. The results are statistically evaluated. Results: The distribution of the A1330V and Q89R genotypes in this population was as follows: AA 81.97%, AV 18.03%, and VV 0.00%; QQ 100%, QR 0.00%, and RR 0.0 0%. No homozygous mutant for A1330V and heterozygous or homozygous mutant for Q89Rare detected in this population. Both the polymorphisms in this population are in Hardy-Weinberg equilibrium. The genotype distributions of rs3736228 showed difference between the osteoporotic patients and control groups [odds ratio (OR):1.98, 95% confidence interval (CI): 0.51 to 7.71, p=0.374]. DNA sequencing of exon 18 not only confirms the presence of A1330V in Indian population but also identifies a novel mutation. Conclusions: The odds ratio (OR) suggests a positive trend toward an association between the A1330V variant and osteoporosis risk. Exon 18 of LRP5 demands special scientific attention. No variation is detected for rs41494349 in the study population.